(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2023)
The article is devoted to the analysis of the relationship between financial motivational mechanisms and employee performance at food industry enterprises. The study examines statistics for the period from 2000 to 2021, including information on investment costs and benefits received, expressed in millions of soums. Based on quantitative analysis, the article evaluates the correlation between the level of investment in employee motivation and employee performance, and also calculates return on investment (ROI). The results of the correlation analysis showed a strong positive relationship, indicating that an increase in investment in financial incentives is closely related to an increase in the benefits received by the enterprise. However, the observed decline in ROI in recent years highlights the need for a better understanding of motivation mechanisms and their impact on performance.